2018
DOI: 10.1099/jmm.0.000788
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae, a 5-year study in a French ICU

Abstract: hvKp represent a potentially underestimated cause of fatal infections in the Western world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 43 publications
5
35
0
1
Order By: Relevance
“…Global dissemination of hvKp. Following early reports of hvKp in Asia, it is now apparent that hvKp has spread globally, including India [163,164], Europe [32,34,35,37,[165][166][167][168], Australia [169,170] and the United States [5,30,31,36,53,171,172] and healthcare providers worldwide should recognize the threat of community-acquired hvKp in otherwise healthy individuals. The rise of hospital-acquired hvKp which may manifest in different presentations, and the convergence of multidrug resistance (MDR) and virulence either in as well as bla SHV-1 and fosA [182] AR, antimicrobial resistance; bla, beta-lactamase provides resistance to penicillins, first-and second-generation cephalosporins; bla CTX-M-24, bla CTX-M-3 and bla CTX-M-4 , ESBLs with particular activity against cefotaxime; bla KPC-2, bla (K. pneumoniae carbapenem resistance) with carbapenemase activity; bla NDM-1 , bla (New Delhi metallo-bla) with carbapenemase activity; bla OXA-32 and bla OXA-9 , ESBLs with particular activity against oxacillin; bla SHV-36 and bla SHV-11 , ESBLs; bla TEM-1A, bla TEM-1, and bla TEM-53 , ESBLs; dfrA14, trimethoprim resistance gene; ESBL, extended-spectrum betalactamase provides additional resistance to monobactams and third-generation cephalosporins; fosA, fosfomycin resistance gene; kb, kilobase, length of DNA molecule; ompK35/36, outer membrane porins that allow entry carbapenems and cephalosporins, reduced expression increases resistance; oqxAB, resistance to olaquindox and some quinolones.…”
Section: Outstanding Questions and Outlookmentioning
confidence: 99%
“…Global dissemination of hvKp. Following early reports of hvKp in Asia, it is now apparent that hvKp has spread globally, including India [163,164], Europe [32,34,35,37,[165][166][167][168], Australia [169,170] and the United States [5,30,31,36,53,171,172] and healthcare providers worldwide should recognize the threat of community-acquired hvKp in otherwise healthy individuals. The rise of hospital-acquired hvKp which may manifest in different presentations, and the convergence of multidrug resistance (MDR) and virulence either in as well as bla SHV-1 and fosA [182] AR, antimicrobial resistance; bla, beta-lactamase provides resistance to penicillins, first-and second-generation cephalosporins; bla CTX-M-24, bla CTX-M-3 and bla CTX-M-4 , ESBLs with particular activity against cefotaxime; bla KPC-2, bla (K. pneumoniae carbapenem resistance) with carbapenemase activity; bla NDM-1 , bla (New Delhi metallo-bla) with carbapenemase activity; bla OXA-32 and bla OXA-9 , ESBLs with particular activity against oxacillin; bla SHV-36 and bla SHV-11 , ESBLs; bla TEM-1A, bla TEM-1, and bla TEM-53 , ESBLs; dfrA14, trimethoprim resistance gene; ESBL, extended-spectrum betalactamase provides additional resistance to monobactams and third-generation cephalosporins; fosA, fosfomycin resistance gene; kb, kilobase, length of DNA molecule; ompK35/36, outer membrane porins that allow entry carbapenems and cephalosporins, reduced expression increases resistance; oqxAB, resistance to olaquindox and some quinolones.…”
Section: Outstanding Questions and Outlookmentioning
confidence: 99%
“…In Asian countries, such as Taiwan, Cambodia, and Shanghai, K. pneumoniae has been described as a frequent cause of bacteremia [26,27]. By contrast, CAP caused by K. pneumoniae is generally rare in Europe and USA, despite there being an increasing incidence in these regions over recent years [28,29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although detailed clinical information was not included in all studies (n = 33), we found that this strain was mainly associated with pneumonia (especially CAP) and other infections are described as follows; CAP (n = 9), hospital-acquired pneumonia (n = 4), bacteremic pneumonia (n = 3, the types of pneumonia are unknown), bacteremia (n = 3, infectious origin is unknown), liver abscess (n = 3), meningitis (n = 2), urinary tract infection (n = 2), wound (n = 2), ventilator-associated pneumonia (n = 1), aspiration pneumoniae (n = 1), abscess (n = 1, origin is unknown), endocarditis (n = 1), and biliary tract infection (n = 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30] Our study has certain limitations. Firstly, this is a single-case report presenting minimal data.…”
Section: Discussionmentioning
confidence: 92%
“…Although data are limited, we found other HV-KP CAP cases in past reports. [17][18][19][20] Including our case, we analyzed ten adult patients with CAP due to HV-KP (Table 1). In our review, the average age was 66.3 (range, 39-90) and the prevalence of CAP due to HV-KP was slightly higher in males (70%).…”
Section: Discussionmentioning
confidence: 99%